2010
DOI: 10.1021/bi100639q
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Binding Sites of Phenolic Herbicides in the QB Pocket of Photosystem II

Abstract: Herbicides targeting photosystem II (PSII) block the electron transfer beyond Q(A) by binding to the Q(B) site. Upon binding, the redox potential of Q(A) shifts differently depending on the types of herbicides. In this study, we have investigated the structures, interactions, and locations of phenolic herbicides in the Q(B) site to clarify the molecular mechanism of the Q(A) potential shifts by herbicides. Fourier transform infrared (FTIR) difference spectra upon photoreduction of the preoxidized non-heme iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
83
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(97 citation statements)
references
References 51 publications
13
83
0
Order By: Relevance
“…This is in line with outcomes from FTIR studies in which the H-bond strength between D1-His215 and Q B could alter the H-bond strength in the Q A side and shift ΔE m (Q A ) PQfBR . 12,13 Similar control modes (the H-bond network between Q A and Q B via Fe) have been reported for the bacterial photosynthetic reaction centers. 28À33 Protein Components That Decrease ΔE m (Q A ).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…This is in line with outcomes from FTIR studies in which the H-bond strength between D1-His215 and Q B could alter the H-bond strength in the Q A side and shift ΔE m (Q A ) PQfBR . 12,13 Similar control modes (the H-bond network between Q A and Q B via Fe) have been reported for the bacterial photosynthetic reaction centers. 28À33 Protein Components That Decrease ΔE m (Q A ).…”
supporting
confidence: 65%
“…Takano et al 12 showed that the H-bonding interaction of Q A is altered by binding of different types of herbicides at the Q B site. Takahashi et al 13 also reported that D1-His215, which donates an H-bond to Q B in the native PSII, forms an H-bond with the phenolate oxygen of the deprotonated BR ( Figure 1) in BR-bound PSII and presented the structural models of herbicide binding in the Q B pocket based on the FTIR results and docking calculations. The latter authors concluded that the strength of the H-bond between D2-His214 and Q A is affected by the interaction between D1-His215 and an herbicide at the Q B site through the Q A ÀHisÀFeÀHisÀherbicide bridge.…”
mentioning
confidence: 99%
“…Figure 3 shows flash-induced FTIR difference spectra of the O 2 -evolving (a, black line) and Mn-depleted (c, red line) PSII membranes of spinach at pH 6.5 measured in an electrolytic solution at +600 mV (vs. SHE) [28]. Bands at 1339, 1258, 1229, 1109, and 1101 cm −1 , which were observed in both spectra, are typical of the Fe 2+ /Fe 3+ difference signals [4,22,44,60,61]. The 1339(+)/1229(−) cm −1 bands were attributed to the symmetric CO stretching vibrations of the bicarbonate ligand [22], while the positive band at 1258 cm −1 and a part of the 1229 cm −1 negative band were assigned to the CO stretching vibration of a Tyr side chain (either D1-Tyr246 or D2-Tyr244) structurally coupled to the non-heme iron using [4-13 C]Tyr labeling [60].…”
Section: Ftir Spectroelectrochemical Study On the Non-heme Ironmentioning
confidence: 96%
“…However, under oxidative conditions, e.g., in the presence of ferricyanide, the non-heme iron is oxidized to Fe 3+ and serves as an endogenous electron acceptor, and hence Fe 3+ is re-reduced to Fe 2+ by light illumination. This photoreaction allows the measurement of a light-induced FTIR difference spectrum of the non-heme iron to investigate the structures of the nearby protein moieties involving the Q B binding site [4,22,44,60,61]. Utilizing the light-induced Fe 2+ /Fe 3+ measurement in combination with the spectroelectrochemical method, we recently studied the effects of the depletion of the Mn 4 CaO 5 cluster on the redox and structural properties of the non-heme iron [28].…”
Section: Ftir Spectroelectrochemical Study On the Non-heme Ironmentioning
confidence: 99%
“…Phenolic commercial herbicides are commonly used in production agriculture (i.e. bromoxynil and isonil) (Takahashi et al, 2010).…”
Section: Sugarcane and Allelopathymentioning
confidence: 99%